Plant species-specificity of ant-plant mutualistic interactions: Differential predation of termites by Camponotus crassus on five species of extrafloral nectaried plants - Calixto, Eduardo; Lange, Denise; Moreira, Xoaquín; Del-Claro, Kleber (Dryad, 2021)
There is increasing evidence that the outcomes of mutualistic interactions
between ants and plants bearing extrafloral nectaries (EFNs) is
context-dependent. In particular, the total number, density and size of
EFNs, as well as the abundance and identity of ants attending host plants,
are considered as key factors determining the nature and strength of
ant-EFN-bearing plant interaction. Although many previous studies have
investigated context-dependency in ant–plant protection mutualisms
mediated by EFNs, few have tested whether the protective behavior of ants
varies among sympatric plant species. In this study, we performed a field
experiment to investigate the predatory behavior of a dominant ant species
(Camponotus crassus, Formicinae) among five EFN-bearing plant species
growing in the Brazilian savanna. In particular, we studied the variation
in the ant abundance, termite predation and time spent to find termites
of C. crassus among the plant species, and further
analyzed whether this variation could be related to the extrafloral nectar
volume and sugar concentration of each plant species. We found that
abundance and termite predation of C. crassusmarkedly varied
among plant species. Specifically, C. crassus ants were
significantly more abundant, active, and protective in Qualea
multiflora, the plant species that produced
significantly higher volumes and sugar concentrations of
nectar. Overall, our results suggest that variation in
extrafloral nectar volume and sugar concentration can result in plant
species-specificity of defensive behavior of a dominant foliage-dwelling
ant in the Brazilian savanna.
1. Study area, plant species and ant species The fieldwork was conducted
in the Ecological Reserve of the Clube de Caça e Pesca Itororó de
Uberlândia (18º58’59”S; 48º17’53”W) in Uberlândia, Brazil. The reserve is
located in a tropical savanna ecoregion (called
Cerrado) (Oliveira & Marquis 2002) and has about
200 ha of cerrado sensu stricto vegetation (specific vegetation of
Cerrado). The cerrado sensu stricto vegetation contains palm swamp areas,
open areas with shrubs and small trees, and more enclosed areas with trees
reaching up to 15 m in height (Del-Claro et
al. 2019). In this region, there is a marked rainy season from
October to March and a marked dry season from April to
September (Alvares et al. 2013,
Novaes et al. 2020, Calixto, Novaes, dos
Santos, et al. 2021). The mean annual
temperature varies from 18 to 28º C and annual rainfall varies from 800 to
2,000 mm (Ferreira & Torezan-Silingardi 2013). For this
study, we selected five of the most abundant EFN-bearing woody species in
our study area (Appolinario & Schiavini
2002): Banisteriopsis malifolia Nees &
Mart. (Malpighiaceae), Lafoensia pacari (A.
St.-Hil.) (Lythraceae), Ouratea spectabilis (Mart.)
Engl. (Ochnaceae), Qualea multiﬂora (Mart.)
(Vochysiaceae) and Stryphnodendron polyphyllum (Mart.)
(Fabaceae). All the plant species exhibit active EFNs on newly flushed
leaves at the beginning of the rainy season
(September-October) (Lange et al. 2013,
Calixto, Novaes, dos Santos, et al. 2021) and
largely vary in production (volume and sugar concentration) and structure
(size and type) of EFNs (Table 1). Because plants continuously
produce new leaves, EFNs are present on the same individual plants for
months. Rainfall events rarely remove extrafloral nectar. The EFNs of
these plant species are frequently visited by Camponotus
crassus (Formicinae) ants (Nahas et al.2012,
Anjos et al. 2017, Lange et al. 2017,
2019, Pires et al. 2017). This ant species
exhibits an aggressive behavior against insect
herbivores (Fagundes et al. 2017,
Lange et al. 2019, Sousa-Lopes et
al. 2020), which usually results in lower levels of herbivory and
higher fruit production compared to plants without ants
(Calixto et al. in review). Due to its numerical abundance and
aggressive behavior, C. crassus is the dominant ant
species on EFN-bearing plants in the Cerrado (Nahas et
al. 2012, Anjos et al. 2017, Lange et
al. 2017, 2019, Pires et
al. 2017). Only few other ant species (usually
subordinate and docile ants) are allowed to forage on the same plant
individuals where C.
crassus monopolizes (Calixto et al. in review;
Fagundes et al. 2016). Therefore, fitness (e.g.
herbivory rate and fruit production) of EFN-bearing plants
hosting C. crassus ants would largely depend on the
protective behavior of this ant species.  2. Data collection In
October 2017, i.e., during the rainy season and when most plants had
active EFNs (Lange et al. 2013, Calixto,
Novaes, dos Santos, et al. 2021), we selected 20
individuals of each plant species (n = 100 individuals) with similar
height (1.5-2 m), separated by at least 10 m, and dominated by C.
crassus ants. In each individual plant, we selected the first
leaf of an apical branch without marks of herbivore damage. Between 09:00
h and 11:00 h, we added an alive worker
of Nasutitermes sp. (Isoptera: Termitidae) collected
from three nests to conduct a termite predation experiment. Termites were
gently captured with the help of tweezers, and without hurting them, they
were placed on the plants. The predation of termite
baits has been widely used as a proxy of ant
effectiveness against herbivores in many plant
taxa (Saks & Carroll 1980, Oliveira et
al. 1987, Oliveira 1997, Apple & Feener 2001,
Anjos et al. 2017, Fagundes et
al. 2017, Cruz et al. 2018, Pacelhe et
al. 2019, Raupp et al. 2020). In order
to avoid biases on encounter time, we only added termites on plants with
at least one individual of C. crassus foraging on it,
and when all C. crassus individuals patrolling the plant
were at least 30 cm away from the selected leaf.  After adding
the termite, we waited for 30 sec until acclimatization and started the
observation. We observed termites for a maximum of 15 min (if there was no
predation event during that time window), and during this time we counted
total C. crassus ant abundance on the whole plant, the
time spent by C. crassus ants to find the termite, and
the termite survival probability (1 = alive and 0 = preyed) or the termite
predation (1 = preyed and 0 = not preyed) by C.
crassus ants. We assume that there were no major changes in the
total number of ants during the 15 min of experiment.
Moreover, C. crassus ants usually do not remove
termites from the plant (take and throw the termite out of the plant), but
they prey on them (Lange et al. 2019).
Therefore, the termite predation parameter was represented by the act of
attacking and taking termites to the nest by ants. Because we aimed at
evaluating the time spent by ants to find termites and (after finding
them) the predation/removal rate, termites have to remain on the plants to
be found by ants. If the termite fell from the plant, we discarded the
observation and started again.
Keywords: ant-plant mutualism; biotic defence; Cerrado; Camponotus crassus; Extrafloral nectar; indirect defense; Protective effectiveness